Modeling and Optimization of Advanced Manufacturing Processes - Bhowmik, Sumit; Jagadish; Gupta, Kapil (Manufacturing and Surface Engineering, 2019)
This book covers various multiple-criteria decision making (mcdm) methods for modeling and optimization of advanced manufacturing processes (AMPs). Processes such as non-conventional machining, rapid prototyping, environmentally conscious machining and hybrid machining are finally put together in a single book. It highlights the research advances and discusses the published literature of the last 15 years in the field. Case studies of real life manufacturing situations are also discussed.